Integrasi Ekonomi Kreatif dan Industri Halal di Indonesia Perspektif Regulasi dan Kebijakan Publik - Rafi Alkaf Asy Syafi; Hendri Hermawan Adi Nugraha (JIOSE: Journal of Indonesian Sharia Economics, 2026)
This study aims to analyze the integration of the creative economy and the halal industry in Indonesia from the perspective of regulation and public policy. The method employed is a qualitative literature review, based on the analysis of academic literature, government regulations, and relevant official reports. The results indicate that the creative economy and the halal industry are strategic sectors with significant contributions to national economic growth and substantial opportunities in the global market. Various regulations, such as the Law on Creative Economy and the Law on Halal Product Assurance along with their implementing policies, have supported the development of an ecosystem that fosters the integration of these sectors through halal certification, intellectual property protection, digitalization, and supply chain strengthening. However, several challenges remain, including low halal literacy among micro, small, and medium enterprises (UMKM), high certification costs, and the lack of optimal policy harmonization across sectors and regions. Therefore, inclusive, adaptive, and collaborative public policies are needed to strengthen the synergy between the creative economy and the halal industry. With effective regulatory support, Indonesia has strong potential to become a globally competitive and sustainable halal creative economy hub.